2017
DOI: 10.1111/jog.13436
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic imaging using positron emission tomography for gynecological malignancy

Abstract: Imaging has played a pivotal role in the management of gynecological malignancy. Positron emission tomography (PET), particularly 18 F-fluorodeoxyglucose ( 18 F-FDG) PET to reflect cellular glycolytic metabolism, is being increasingly used and has proven superior to conventional imaging including ultrasonography, computed tomography (CT), and magnetic resonance imaging. Studies of and evidence for the utility of 18 F-FDG PET/CT for the detection of local or metastatic disease, treatment planning, response asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 133 publications
(294 reference statements)
0
14
0
Order By: Relevance
“…It has been generally accepted that 18F-FDG-PET/CT has higher diagnostic performance than CT or MRI in detecting metastatic lymph nodes in gynecological cancer patients 26 . Although it has been reported that 18F-FDG-PET/CT reliably detects lymph node deposits with a volume larger than 80 mm 3 27 , false-positive detection of lymph node involvement has been caused by benign conditions, including systemic inflammation, infectious diseases, or immunizations 28 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been generally accepted that 18F-FDG-PET/CT has higher diagnostic performance than CT or MRI in detecting metastatic lymph nodes in gynecological cancer patients 26 . Although it has been reported that 18F-FDG-PET/CT reliably detects lymph node deposits with a volume larger than 80 mm 3 27 , false-positive detection of lymph node involvement has been caused by benign conditions, including systemic inflammation, infectious diseases, or immunizations 28 .…”
Section: Discussionmentioning
confidence: 99%
“…For the detection of lymph node metastasis, distant metastasis, peritoneal disease or recurrent disease in ovarian cancer, 18 F-FDG PET/CT could be useful compared with conventional modalities including CT or MRI (6)(7)(8)(9)(10). However, 18 F-FDG PET/CT has a limited and controversial role to play in the characterization of ovarian tumors, because the physiologically increased uptake of FDG into the normal ovaries leads to false-positive results or low diagnostic value in differentiating between borderline and benign tumors due to low FDG uptake leading to false-negative results (11).…”
Section: Introductionmentioning
confidence: 99%
“…MRI constitutes the gold standard for the characterization of suspected ovarian malignancy, and MRI with intravenous contrast administration provides the highest post-test probability of detecting ovarian cancer, compared with CT, US with color Doppler or MRI without contrast administration(3). The utility of 18 F-FDG PET/CT in the differentiation of benign and malignant ovarian tumors is reportedly limited because of false-positives resulting from physiological conditions such as in ammation or the menstrual cycle and false-negatives in diagnosing early-stage or borderline malignancies(11). In terms of 18 F-FDG PET/MRI, only fused 18 F-FDG PET/MRI…”
mentioning
confidence: 99%
“…For the detection of lymph node metastasis, distant metastasis, peritoneal disease or recurrent disease in ovarian cancer, 18 F-FDG PET/CT could be useful compared with conventional modalities including CT or MRI (6)(7)(8)(9)(10). However, 18 F-FDG PET/CT has a limited and controversial role to play in the characterization of ovarian tumors, because the physiologically increased uptake of FDG into the normal ovaries leads to false-positive results or low diagnostic value in differentiating between borderline and benign tumors due to low FDG uptake leading to false-negative results (11).…”
Section: Introductionmentioning
confidence: 99%